Classic star wars : Luke's fate - Thomas, Jim K., 1970-; Lucas, George, 1944-; Mones, Isidre (New York : Random House, 1996)
1. Robots--fiction 2. Science--Fiction
Basic ed. students
Keywords: Robots -- Fiction; Science fiction